Behavioral influences in credit card usage and shopping attitudes: a survey - Erdoğan, Esra (My University, 2009)
Kredi Kartı Kullanımı ve Alışveriş Tutumları Üzerindeki Davranışsal Etkiler: Bir Anket Bu tezin amacı “ İnsanlar kredi kartı kullanımlarında ve alışveriş tutumlarında düşünmeden tepkisel davranırlar mı ve bazı davranışsal önyargılara sahipmidirler” sorusuna cevap bulmaktır. Davranışsal finans teorileri tarafından önerildiği üzere insanlar finansal karar alma süreçlerinde bilişsel önyargılar ve etkinsizlikler altında hareket ederler. Bu cevapları bulabilmek amacıyla, demografi için onaltı tane ve insanların günlük yaşamlarında finansal karar alırken karşılaştıkları davranışsal önyargılar ve tepkisellik seviyelerini ölçmek için yirmi sekiz tane olmak üzere toplam kırk dört soruluk bir anket hazırlandı. Anket bir alışveriş merkezinde gerçekleştirildi ve denekler büyük bir mağazanın müşterileriydi. Sonuçlar gösterdi ki, bireyler kredi kartı kullanırken ve alışveriş yaparken tepkisel davranırlar ve aynı tutumları sergilerler.

Behavioral Influences in Credit Card Usage and Shopping Attitudes: A Survey Esra Erdogan Associate Prof. Dr. Jale Sozer Oran The aim of this dissertation is to find answers to these two questions “Do people behave impulsively in credit card usage and shopping attitudes”, and “Do people have some of behavioural biases in their credit card usage and shopping attitudes.” As suggested by behavioral finance theories, people are acting under cognitive biases and inefficiencies in their financial decision-making processes. It might also be true that credit card usage and shopping decisions have similar inefficiencies. In order to find these answers, a questionnaire is prepared which consists of sixteen demographic questions and twenty-eight questions to measure the impulsivity levels of people and whether or not individuals have behavioural biases when they face with financial decision making need in their everyday life. Survey is conducted in a mall, and the subjects were the customers of a big department store. Results show that individuals are acting on impulses and demonstrate similar attitudes while shopping and using credit cards.
Keywords: Kredi Kartları; Muhasebe